2011
DOI: 10.1007/s00586-011-1868-5
|View full text |Cite
|
Sign up to set email alerts
|

Intervertebral disc changes with angulation, compression and reduced mobility simulating altered mechanical environment in scoliosis

Abstract: Purpose The intervertebral discs become wedged and narrowed in scoliosis, and this may result from altered biomechanical environment. The effects of four permutations of disc compression, angulation and reduced mobility were studied to identify possible causes of progressive disc deformity in scoliosis. The purpose of this study was to document morphological and biomechanical changes in four different models of altered mechanical environment in intervertebral discs of growing rats and in a sham and control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Manual tracing is a relatively common method used to determine fiber orientation in soft collagenous tissues [33][34][35], and permits comparing with a reference set by an expert. We conducted three test cases: loaded tendon fibers, a single curved silk fiber, and a sample of cornea from an eye at high intraocular pressure.…”
Section: Accuracy In Tendon Single Fibers and Corneamentioning
confidence: 99%
“…Manual tracing is a relatively common method used to determine fiber orientation in soft collagenous tissues [33][34][35], and permits comparing with a reference set by an expert. We conducted three test cases: loaded tendon fibers, a single curved silk fiber, and a sample of cornea from an eye at high intraocular pressure.…”
Section: Accuracy In Tendon Single Fibers and Corneamentioning
confidence: 99%
“…The mechanism by which the discs become wedged is poorly understood. Endplate calcification has been observed in discs of humans with scoliosis and in a porcine model of induced scoliosis, and is considered as a possible cause of nutritional compromise and consequent disc degeneration and wedging in scoliosis [3032]. But we did not do examinations on endplate calcification for patients with AIS routinely.…”
Section: Discussionmentioning
confidence: 99%
“…But we did not do examinations on endplate calcification for patients with AIS routinely. Stokes et al [32] reported that reduced mobility was a major source of disc changes and may be a factor in disc deformity. In the previous literature, posterior procedure fused more motion segments and reduced more mobility compared with anterior procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a surrogate scoliosis model, we have chosen to use a calf spine model, which, although possessing an anatomy and vertebral kinematics similar to those of a normal human spine, 3,6 cannot simulate the rotational deformation and altered geometry and mechanics of the vertebrae and of the intervertebral discs that are typical of a scoliotic spine. 19,21,30,31 In particular, the wedging of the vertebrae and discs and the reduced mobility exhibited by scoliotic spines will cause significant lateral deformation of the spine and altered intersegmental stiffness throughout the spine, both of which are not accounted for in our model. 21 As demonstrated in the current study, local changes in the boundary conditions and kinematical constraints of the instrumented vertebra will significantly affect the obtained derotation of the vertebrae for a given rotation imparted by the surgeon.…”
Section: Discussionmentioning
confidence: 99%